A Cohort Retrospective Study of Framingham Score and ECG Abnormality among Coal Mining Workers - Anandita, Faizal Ablansah; Firdaus, Isman; Gani, Rino Alvani; Werdhani, Retno Asti; Mansyur, Muchtaruddin (UI Scholars Hub, 2023)
Introduction. ECG is widely used for detecting cardiovascular disease in coal mine worker’s medical check-up. As the study has proven, coal mine workers have a double cardiovascular risk from their workplace hazard and their own medical risks as individuals. An early detection and risk assessment method is needed to predict ECG abnormalities in the future. This study will analyze the relationship between ECG abnormality and Framingham Risk Score on coal mine workers’. Methods. We examine ECG result from medical check-up of male coal worker during 2018 and 2021. Using Minnesota Code, we determine ECG abnormality categories in the 2021 result, then compare it with coal handling type worker and Framingham Score in 2018 as the main medical factor. Results. Among 755 male coal workers with normal ECG in 2018, 158 (20,9%) were found with ECG abnormalities in 2021. Cohort’s multivariate study shows that type of coal worker is considered a determinant, but Framingham risk score still has the highest influence (p multivariate